Kajian Biblika berdasarkan Daniel 12 terhadap Tanda-tanda tentang Akhir zaman - Yosua Tabuni (Jurnal Teologi (JUTEOLOG), 2021)
This paper aims to find out the signs of the end times based on Daniel 12, using a hermeneutic approach and library research, this writing finds that the signs in Daniel 12 are a sign of emphasizing that in the last days there will be extraordinary tribulations that are misery that has never been and will not have happened since the existence of the world.Michael will appear as a prince to the righteous and every believer will escape the tribulation.